2023
DOI: 10.1186/s12929-023-00920-8
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the RNA-binding protein PUM2 facilitates MSC-driven bone regeneration and prevents OVX-induced bone loss

Abstract: Background Although mRNA dysregulation can induce changes in mesenchymal stem cell (MSC) homeostasis, the mechanisms by which post-transcriptional regulation influences MSC differentiation potential remain understudied. PUMILIO2 (PUM2) represses translation by binding target mRNAs in a sequence-specific manner. Methods In vitro osteogenic differentiation assays were conducted using human bone marrow-derived MSCs. Alkaline phosphatase and alizarin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…The ability of the nano‐micro CaP@MS‐Oligo‐Van composites to stimulate the mineralization of BMSCs was further analyzed using Alizarin Red S staining. [ 58 ] CaP@MS and CaP@MS‐Oligo‐Van generated a substantial number of mineralized nodules (Figure 5d ). Quantitative analysis confirmed that the composites containing CaP nanosheets could improve osteogenic activity in BMSCs (Figure 5e ).…”
Section: Resultsmentioning
confidence: 99%
“…The ability of the nano‐micro CaP@MS‐Oligo‐Van composites to stimulate the mineralization of BMSCs was further analyzed using Alizarin Red S staining. [ 58 ] CaP@MS and CaP@MS‐Oligo‐Van generated a substantial number of mineralized nodules (Figure 5d ). Quantitative analysis confirmed that the composites containing CaP nanosheets could improve osteogenic activity in BMSCs (Figure 5e ).…”
Section: Resultsmentioning
confidence: 99%
“…The potential of the bone fibril-like scaffold for the osteogenic differentiation of BMSCs was explored. Alkaline phosphatase (ALP) is an early biomarker of the osteogenic phenotype and plays a critical role in the initial stage of bone formation. , As shown in Figure A, the deepest ALP staining is found for BMSCs after they were cocultured for 7 days with MNTS. Alizarin Red S staining was also conducted on day 14 to determine whether mineralized nodules were present during late osteogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…As described above, in bone physiology PUM2 is essential to maintain balance in the MSCs differentiation, and, for this reason, it could have a potential role in OP ( Spassov and Jurecic, 2003 ). In this regard, Yoon et al (2023) , identified PUM2 as a potential therapeutic target for bone-related diseases, including OP. By performing in vivo experiments on a rat model of calvarial defects and on an OVX mice model of postmenopausal OP, the authors have observed that a KO of PUM2 and systemic delivery of PUM2 siRNA prevented bone loss, promoting respectively bone regeneration and alleviation of OP symptoms.…”
Section: Role Of Rbps In the Bone Pathologiesmentioning
confidence: 99%